Betting men's ideas on İDDAA (Turkey's Official Football Betting Game) - Coşkuner, Zeki (My University, 2013)
Football is a popular culture area that comes into our lives further day by day and has much more place in life as well. Football legitimates its dominance that achieves dominance all around the world, over Turkey, too. Society's ideas on football changes into from football lovers point to football society. Sport spectators' reasons of watching competitions vary. These are thought as amusement, social identity, discharges and materialistic expectation. On materialistic expectation, İddaa (betting game), Sport Toto (football pool), Sport Lotto (lotto) and Horse Racing are ale to be evaluated as to supply materialistic expectations. In this study, a questionnaire forms from 73 question which is 8 questions are on demographic information is applied on 1080 betting men in Elazi{dotless}? province. Aim of the study is to determine betting men's psychological and sociological expectations from betting game which is the most common way of supplying materialistic expectation at materialistic expectation ways at sports and their ideas on media and match fixing rumors. As a result, when general averages are calculated at the study in which 5 point likert scale is used, prominent factors are like below: %84.4 of participators are between 18-25 year-old age range, %83.8 of them earn their least income from betting game and %74's of them state that they do not earn money from betting game. Whereas participators express "I agree." on (X?:4.15) portion on question of "Earning money easily plays important role on spreading this game of chance.", they state that "Newspapers play important game on popularizing the game." (X?:4.23). Factor of "Government should tighten up control of age limit." is shown as (X?:3.93), "Governors support this games because government earn money from this games." is followed by (X?:4.23) factor. It is turned out that "Participators believe in that there is match fixing at some matches." (X?:3.96), "Believing in footballers fix some matches" (X?:3.95), "Believing in referee fixes at some matches" (X?:3.92), "Believing in club managers fix matches at some matches" (X?:3.91) factors are followed by least differences.
Keywords: Bet; Football; Gamble; Game; İddaa (betting game)